IB4‐binding sensory neurons in the adult rat express a novel 3′ UTR‐extended isoform of CaMK4 that is associated with its localization to axons. Issue 2 (February 2014) - Harrison, Benjamin J.; Flight, Robert M.; Gomes, Cynthia; Venkat, Gayathri; Ellis, Steven R.; Sankar, Uma; Twiss, Jeffery L.; Rouchka, Eric C.; Petruska, Jeffrey C.
ABSTRACT Calcium/calmodulin‐dependent protein kinase 4 (gene and transcript: CaMK4; protein: CaMKIV) is the nuclear effector of the Ca2+/calmodulin kinase (CaMK) pathway where it coordinates transcriptional responses. However, CaMKIV is present in the cytoplasm and axons of subpopulations of neurons, including some sensory neurons of the dorsal root ganglia (DRG), suggesting an extranuclear role for this protein. We observed that CaMKIV was expressed strongly in the cytoplasm and axons of a subpopulation of small‐diameter DRG neurons, most likely cutaneous nociceptors by virtue of their binding the isolectin IB4. In IB4+ spinal nerve axons, 20% of CaMKIV was colocalized with the endocytic marker Rab7 in axons that highly expressed CAM‐kinase‐kinase (CAMKK), an upstream activator of CaMKIV, suggesting a role for CaMKIV in signaling though signaling endosomes. Using fluorescent in situ hybridization (FISH) with riboprobes, we also observed that small‐diameter neurons expressed high levels of a novel 3′ untranslated region (UTR) variant of CaMK4 mRNA. Using rapid amplification of cDNA ends (RACE), reverse‐transcription polymerase chain reaction (RT‐PCR) with gene‐specific primers, and cDNA sequencing analyses we determined that the novel transcript contains an additional 10 kb beyond the annotated gene terminus to a highly conserved alternate polyadenylation site. Quantitative PCR (qPCR) analyses of fluorescent‐activated cell sorted (FACS) DRG neurons confirmed that this 3′‐UTR‐extended variant was preferentially expressed in IB4‐binding neurons. Computational analyses of the 3′‐UTR sequence predict that UTR‐extension introduces consensus sites for RNA‐binding proteins (RBPs) including the embryonic lethal abnormal vision (ELAV)/Hu family proteins. We consider the possible implications of axonal CaMKIV in the context of the unique properties of IB4‐binding DRG neurons. J. Comp. Neurol. 522:308–336, 2014. © 2013 Wiley Periodicals, Inc.